A case report of acute inferior myocardial infarction in a patient with severe hemophilia A after recombinant factor VIII infusion. Issue 52 (December 2017) - Zupančić-Šalek, Silva; Vodanović, Marijo; Pulanić, Dražen; Skorić, Boško; Matytsina, Irina; Klovaite, Jolanta
Abstract: Rationale: The extent of protective effects of hemophilia against thrombotic events such as myocardial infarction (MI) and other acute coronary syndromes remains to be determined, as major risk factors for cardiovascular disease exist despite factor VIII (FVIII) deficiency. We present a case report of a 41-year-old male with severe hemophilia A and several cardiovascular risk factors. Patient concerns: This morbidly obese patient developed chest pressure, followed by chest pain and difficulty in breathing shortly after receiving on-demand treatment with intravenous recombinant FVIII (rFVIII) (turoctocog alfa) dosed per body weight. Diagnoses: An electrocardiogram revealed a diagnosis of inferior ST-segment elevation MI. Interventions: The patient underwent an urgent coronary angiography using a radial artery approach. During the next 12 months, he received dual antiplatelet treatment, acetylsalicylic acid 100 mg, and clopidogrel 75 mg daily. His treatment for severe hemophilia A was changed to plasma-derived FVIII replacement therapy. Outcomes: During this 12-month period, he experienced several small bleeds in his elbows. Conclusions: The temporal relationship between rFVIII infusion and onset of the MI suggests a possible association; however, apart from obesity, the patient also had other major risk factors for arterial thrombosis, such as hypertension and smoking. Furthermore, atherosclerotic disease and underlying atherosclerotic changes could not be excluded with certainty. This case highlights the importance of studies assessing the impact of excess body weight on rFVIII dosing.